Women Strategizing Through Inyumba Mboke Marriage in Tanzania - Mhando, Nandera (Tanzania Journal for Population studies and Development, 2014)
This article explores the politics of a wife’s house and ways in which women act to maintain or build their ‘houses’. Inyumba mboke marriagesconsist of two Kuria words: inyumba, meaning the physical house, and also referring to a mother and her children; and mboke, which refers to the need for that house to stand or progress by marrying a wife to bear children for that house.The paper explains the position that both women and men play in marriage arrangements, and the reasons for continuing the practice. Gender is in some contexts flexible, as there are prospects for negotiation and even change in role and status, rendering gendered identities highly fluid. Yet biological sex is also of enormous significance because only women can give birth to children. Thus, infertility and even death can be overcome as sonless or childless women (dead or alive), and dead men may acquire offspring. In this regard, rather than seeing these relationships as ‘woman-to-woman marriage’ or ‘ghost marriage’, this study suggests that they comprise various different kinship and marriage relations that allow women to reproduce for the lineage, and to make descendants for themselves, even in the absence of husbands, lovers, and/or ‘real’ sons.